Representation of Cultural Identity in Contemporary English Literature: A Narrative Analysis of Texts and Young Readers - Lestari, Chatarini Septi Ngudi (Journal of Language Development and Linguistics, 2025)
This study explores the representation of cultural identity in contemporary English literature and its interpretation by young readers. Using a qualitative approach that combines narrative/textual analysis and reader response methods, data were drawn from three contemporary novels and semi-structured interviews with 20 readers aged 18–22, then analyzed through thematic coding and critical interpretation. The findings show that texts construct cultural identities through character portrayals, symbolic settings, and intercultural conflicts, while young readers negotiate these narratives by connecting them to personal experiences and social contexts. The study concludes that literary texts function as both cultural representation and dialogical spaces where readers actively construct meaning, contributing to the reconstruction of cultural identity. Theoretically, it enriches discussions on cultural representation and reader response, while practically highlighting the role of literature in education to foster intercultural understanding and critical awareness.